Concurrent femoral head reduction and periacetabular osteotomies for the treatment of severe femoral head deformities. (December 2018) - Clohisy, J. C.; Pascual-Garrido, C.; Duncan, S.; Pashos, G.; Schoenecker, P. L.
Abstract : Aims: The aims of this study were to review the surgical technique for a combined femoral head reduction osteotomy (FHRO) and periacetabular osteotomy (PAO), and to report the short-term clinical and radiological results of a combined FHRO/PAO for the treatment of selected severe femoral head deformities. Patients and Methods: Between 2011 and 2016, six female patients were treated with a combined FHRO and PAO. The mean patient age was 13.6 years (12.6 to 15.7). Clinical data, including patient demographics and patient-reported outcome scores, were collected prospectively. Radiologicalally, hip morphology was assessed evaluating the Tönnis angle, the lateral centre to edge angle, the medial offset distance, the extrusion index, and the alpha angle. Results: The mean follow-up was 3.3 years (2 to 4.6). The modified Harris Hip Score improved by 33.0 points from 53.5 preoperatively to 83.4 postoperatively (p = 0.03). The Western Ontario McMasters University Osteoarthritic Index score improved by 30 points from 62 preoperatively to 90 postoperatively (p = 0.029). All radiological parameters showed significant improvement. There were no long-term disabilities and none of the hips required early conversion to total hip arthroplasty. Conclusion: FHRO combined with a PAO resulted in clinical and radiological improvement at short-term follow-up, suggesting it may serve as an appropriate salvage treatment option for selected young patients with severe symptomatic hip deformities.